2013
DOI: 10.2337/dc12-1168
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Risk of Fracture-Related Hospitalization

Abstract: OBJECTIVETo examine the association between diabetes, glycemic control, and risk of fracture-related hospitalization in the Atherosclerosis Risk in Communities (ARIC) Study.RESEARCH DESIGN AND METHODSFracture-related hospitalization was defined using International Classification of Diseases, 9th revision, codes (733.1–733.19, 733.93–733.98, or 800–829). We calculated the incidence rate of fracture-related hospitalization by age and used Cox proportional hazards models to investigate the association of diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 25 publications
2
78
0
Order By: Relevance
“…(3) Both diseases are detrimental to the bone resulting in an increased risk for fragility fractures (4) : the lifetime risk to sustain an osteoporotic fracture ranges between 40% to 50% in women (5) and in T2D, the risk of having a fragility fracture lies even higher and varies dependent on the skeletal site between 20% and 160% in elderly women. (6) Given the substantial morbidity, mortality, and costs that emanate from osteoporotic (7) or T2D-related fractures, (8,9) proper recognition of populations at increased fracture risk is indispensable. Areal bone mineral density (aBMD) testing by dual energy X-ray absorptiometry (DXA) and assessment of clinical scores such as the WHO Fracture Risk Assessment Tool (FRAX) are regarded as the international standards for assessment of fracture risk in osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Both diseases are detrimental to the bone resulting in an increased risk for fragility fractures (4) : the lifetime risk to sustain an osteoporotic fracture ranges between 40% to 50% in women (5) and in T2D, the risk of having a fragility fracture lies even higher and varies dependent on the skeletal site between 20% and 160% in elderly women. (6) Given the substantial morbidity, mortality, and costs that emanate from osteoporotic (7) or T2D-related fractures, (8,9) proper recognition of populations at increased fracture risk is indispensable. Areal bone mineral density (aBMD) testing by dual energy X-ray absorptiometry (DXA) and assessment of clinical scores such as the WHO Fracture Risk Assessment Tool (FRAX) are regarded as the international standards for assessment of fracture risk in osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with inadequately controlled T2D had a 47-62% higher fracture risk than those without diabetes despite having 1.1-5.6% higher BMD by DXA [ 20 ]. Similarly, those with glycated hemoglobin (HgA1C) >8.0% had a greater risk of fracture than those with HgA1C <8.0%, suggesting fracture risk is a function of the extent to which hyperglycemia is controlled [ 21 ].…”
Section: Incidence and Contributing Factorsmentioning
confidence: 87%
“…Interestingly, the bone density scan was normal. Cross-sectional epidemiological studies have found that patients with type 2 diabetes mellitus have a higher incidence of fragility fractures despite normal or elevated BMD [3,[8][9][10]. This is likely to be explained by the fact that type 2 diabetes induces deterioration of bone microarchitecture leading to a porous skeleton susceptible to fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Poor diabetes control is also associated with high risk of bone fracture. For instance, the Atherosclerosis Risk in Communities (ARIC) Study showed that type 2 diabetes was significantly and independently associated with increased risk of fracture especially those treated with insulin or those with HbA1c ≥ 8% (64 mmol/L) as compared to those individuals with HbA1c below 8% [9]. Furthermore, the Rotterdam Study data showed that poor glycemic control based on an HbA1c cut-off of 7.5%…”
Section: Introductionmentioning
confidence: 99%